ENHANCING ENGLISH PROFICIENCY AND CHARACTER DEVELOPMENT THROUGH ENGLISH LEARNING PROGRAM AT SMP TERPADU CENDIKIA INSANI - Mochammad Alvin Pratama Putra; Frandini Eris Yudianti; Safira Hariyani Putri (International Journal of Community Service in Language, Literature, Culture, and Their Teaching, 2024)
The community service activities carried out at SMP Terpadu Cendikia Insani aim to enhance students' English language proficiency and character development through structured and collaborative programs. The 'Intensive English Course' program is designed to significantly improve students' speaking, listening, reading, and writing skills in English. The creation of a student wall magazine aims to encourage creativity and the use of English in an enjoyable context, while the literary creation program focuses on developing writing skills and character through reflection and self-expression. Collaboration with parents and the community is also pursued to create a more supportive educational environment. The results of these activities show an improvement in students' English proficiency and interest in literature, as well as active participation from parents and the community. Financial support from Universitas Abdurachman Saleh Situbondo has been crucial to the success of these programs. Overall, this community service initiative has had a significantly positive impact on the academic and character development of students at SMP Terpadu Cendikia Insani.